Current Opportunities and Future Prospects of Neuroprotective Therapy in Glaucoma. Literature Review. Part 1 - N. I. Kurysheva; A. V. Korneeva; S. I. Ponomareva; H. M. Plieva; V. E. Kim; I. D. Kim; M. V. Chebotareva (Oftalʹmologiâ)
This literature review is devoted to one of the most complex ophthalmology problems — neuroprotective and neuroregenerative treatment of glaucoma and consists of two parts. The first part considers the main mechanisms of neurodegeneration and the main aspects of therapeutic control related to these mechanisms (excitotoxicity, mitochondrial dysfunction, oxidative stress). The main aim of the conducted literature analysis is to provide a comprehensive overview of both existing neuroprotective strategies and promising areas of therapy based on neuroprotective agents in the potential treatment of glaucoma. A wide range of approaches to neuroprotection demonstrates the great potential for effective treatment of neurodegeneration in order to preserve visual functions in patients with glaucoma.